Medication Management At Gunung Tinggi Health Center, Medan City - Nazua Nabila; Rista Wahyuni; Rosi Ani Riski; Citra Rahmi Bahar; Anggi Cahya Utari; Indah Doanita Hasibuan (Jurnal EduHealth, 2024)
Medication management at the Gunung Tinggi Community Health Center is an important aspect in providing health services. The aim of this study was to evaluate the drug management process from planning to disposal. The research method used was descriptive and qualitative with in-depth interviews with community health center managers, pharmacy staff and pharmacist leaders. The results of the study show that although there are several obstacles in the procurement and distribution of medicines, the management of medicines at the Gunung Tinggi Community Health Center has been carried out in accordance with applicable standard operating procedures (SOP). Management systems need to be improved to ensure optimal access to medicines.